Left atrial myxoma causing posterior cerebral artery infarct-a case report - Kumar, Sudesh; Bhattacharya, Shubhadev; Jhajhria, Narender S.; Gupta, Vijay Kumar (International Surgery Journal, 2017)
A 34-year-old female patient presented with a history of sudden loss of vision in right eye. On neurological examination, she was having visual agnosia in right eye. MRI was performed which revealed left posterior cerebral artery infarct. Trans thoracic echocardiography was performed. This showed a large left atrial myxoma. Patient underwent resection and had an uneventful postoperative course. This case report showed the importance of cardiac source of emboli in patients presenting as acute stroke. Performing echocardiography and diagnosing and treating cardiac source of emboli could prevent further complications.